Cold-proof Technology on Traction Motor of High-cold CRH380B EMUs - XIANG A-feng; YU Wei-long; CHEN Ming-hui (机车电传动)
According to high-cold CRH380B EMUs used at -40℃ outside temperature, this article put forward the key factors of the traction motor that should be taken into consideration when running in the high-cold environment. By analyzing the harmful effects caused by the cold weather to the key components of traction motor, the article brings cold-proof solutions one by one.